Edukasi Pendidikan Seksual Di Tk Negeri Tirta Kencana - Riski kurniawati; Wulan tania sari; Sofi Saniati; Akhmad Fikri Rosyadi (CV. ITTC INDONESIA, 2024)
This activity is about sexual education at the Tirta Kencana Kindergarten, as for how to educate it through music and movement. The purpose of this education is to provide knowledge to children. Because of the rampant sexual violence that occurs in children today, the growth and development of children now and in the future is very dangerous if children become victims of sexual violence. For this reason, sexual education is provided in schools to prevent sexual violence from occurring. The implementation method used is the educational method through music and songs in the form of counseling. The strategy in this counseling is to provide educational material through movements and songs entitled ku take care of my body for the children. Based on the results of counseling, it shows that children already know what parts of their bodies can and cannot be touched by other people and know what to do if someone else touches them.